2021
DOI: 10.3390/antibiotics10091099
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Characterization of Fecal Extended-Spectrum-Beta-Lactamase-Producing Escherichia coli Isolated from Pigs on Farms of Different Sizes in Latvia

Abstract: The aim of this study was to determine the prevalence of fecal ESBL-producing Escherichia coli (E. coli) in pigs on large and small farms in Latvia, to characterize beta-lactamase genes and establish an antimicrobial resistance profile. Fecal samples (n = 615) were collected from 4-week, 5-week, 6-week, 8-week, 12-week and 20-week-old piglets, pigs and sows on four large farms (L1, L2, L3, L4) and three small farms (S1, S2, S3) in Latvia. ChromArt ESBL agar and combination disc tests were used for the screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In accordance with our previous study, the bla TEM in milk that were collected from the cows was significantly increased ( p < 0.05) after 3 days of cephalosporin exposure [ 25 ]. It was also reported that bla TEM was one of the most abundant ARGs in the feces from a pig farm [ 26 ]. In the present study, the β-lactamase encoding genes bla TEM and cfx A were significantly increased ( p < 0.05) at the withdrawal period.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our previous study, the bla TEM in milk that were collected from the cows was significantly increased ( p < 0.05) after 3 days of cephalosporin exposure [ 25 ]. It was also reported that bla TEM was one of the most abundant ARGs in the feces from a pig farm [ 26 ]. In the present study, the β-lactamase encoding genes bla TEM and cfx A were significantly increased ( p < 0.05) at the withdrawal period.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic bacteria from different sources, like industry, soil and humans, can fuse to hydrous habitants, which causes the high increment in the antibiotic resistance through some genetic mechanism such as transposons and integrons, besides plasmids. In a normal bacterial ecosystem this mutation in bacteria can cause the transformation of bacteria from non-pathogenic to resistant toward antibiotics [6]. Our study aimed to determine the prevalence of some beta lactamase genes (blaTEM, and blaCTX-M) type ESBL variants among E. coli which were collected from some clinical antibiotics resistant isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Three of ESBL-producing isolates were classified as MDR, which contained the following antimicrobial resistance profile: AM-CTX-CZ-AMC-GM-SXT-TMP-C-TE-ENO, and two with AM-CTX-CZ-AMC-GM-SXT-TMP-C-TE, but the other three as non-MDR ESBL-producing E. coli. Finally, the last three E. coli isolates did not show resistance to any of the 18 antibiotics [68].…”
Section: Antibacterial Assays 431 Escherichia Coli Strainsmentioning
confidence: 89%
“…A total of 10 E. coli isolates were used to test the antibacterial properties of EOs. One of the isolates was used as antibiotic-sensitive reference strain ATCC 25922 (Bioscience, Botolph, United Kingdom), but the other isolates were collected from pig faeces according to the methodology described by [68]. Six isolates were ESBL-producing E. coli, containing all of three bla genes: bla CTX-M , bla TEM , and bla SHV .…”
Section: Antibacterial Assays 431 Escherichia Coli Strainsmentioning
confidence: 99%